EFFECTIVE TEACHING STRATEGIES FOR INCREASING STUDENTS’ MOTIVATION IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Jabborova Jasmina Jamshid kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study explores effective teaching strategies that enhance students’ motivation in learning English as a foreign language. Techniques such as communicative activities, task-based learning, and interactive feedback are highlighted for promoting engagement and interest.